The scarring effects of major economic downturns: The role of fiscal policy and government investment - Martin Larch; Peter Claeys; Wouter Van Der Wielen (European Investment Bank (EIB), 2022)
Long shunned as slow and ill timed, the response to the Covid-19 pandemic initiated a reassessment of fiscal policy as stabilisation tool. At the same time, there is ample evidence that major economic downturns produce lasting effects on real GDP in spite of active fiscal policy interventions. This paper takes a fresh look at economic scarring in 26 OECD countries, including 14 EU member states, since 1970 and examines the role played by fiscal policy. We find that higher current expenditure - the favoured active response - does not mitigate the lasting impact of major economic downturns on real GDP. In contrast, more government investment could help but generally receives little attention. As a result, scarring effects are significant confronting governments with higher debt levels, which in turn weigh on the room for manoeuvre in subsequent downturns. In sum, fiscal policy makers face two difficulties in the event of a major economic downturn: (i) adopt the right type of fiscal expansion, and (ii) find the right time to pivot from short-term stabilisation to fiscal consolidation while protecting investment. Both challenges are fraught with political economy issues.
Keywords: E60; E62; E65; H62; 330; scarring effects; major economic downturn; fiscal policy; fiscal stabilisation; public investment